Barack Obama's post-American foreign policy :the limits of engagement - Singh, Robert (London ; New York : Bloomsbury Academic, 2012)
"After one of the most controversial and divisive periods in the history of American foreign policy under President George W. Bush, the Obama administration was expected to make changes for the better in US relations with the wider world. Now, international problems confronting Obama appear more intractable, and there seems to be a marked continuity in policies between Obama and his predecessor. Robert Singh argues that Obama's approach of 'strategic engagement' was appropriate for a new era of constrained internationalism, but it has yielded modest results. Obama's search for the pragmatic middle has cost him political support at home and abroad, whilst failing to make decisive gains. Singh suggests by calibrating his foreign policies to the emergence of a 'post-American' world, the president has yet to preside over a renaissance of US global leadership. Ironically, Obama's policies have instead hastened the arrival of a post-American world." -- Publisher's website.
A Post-American Foreign Policy for the Post-American World -- The "Human Ink-Blot": Obama, foreign policy and the 2008 election -- The Obama Doctrine: "leading from behind" -- Afghanistan, Pakistan and the War on Terror -- Iran -- Israel, Palestine and the Arab Spring -- China -- Russia -- Keep the Change: Continuity We Can Believe In.
Includes bibliographical references (p. 203-242) and index.
Keywords: Obama, Barack; United States -- Foreign relations -- 2009-; United States -- Politics and government -- 2009-